Birds-eye view of Alaska Yukon Pacific Exposition
Drawing of exposition buildings surrounded by trees and water; mountains in distance. Inscription reads "Birds eye view of the Alaska-Yukon Pacific Exposition grounds, Seattle, Wn. 1909."